Object-Oriented Publish/Subscribe System - Biao Dong (Institute of Advanced Engineering and Science, 2014)
Existing methodologies based on the request/response model for system software design, rooted in principles of object-oriented design, lead to tightly-coupled interactions, and lack coordination capacities. The publish/subscribe(P/S) paradigm is particularly suitable for loosely- coupled communication environment. A design of event and subscription models under an object- oriented environment was motivated by the idea of using P/S paradigm for an object-oriented environment. The P/S service is comprised of two subsystem-compiler and executor. In each subsystem, its form, working process, and typical algorithms are analysed from the point of object-oriented and technology of P/S paradigm separately. Experiment was simulated in the following two aspects: user’s model and middle code generation, and shows that using the P/S service improves the usability of P/S systems. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5391